The Impact of E-Learning on Teaching Management of Primary Education in Rwanda - Ruth, Mbabazi (International Journal of Scientific Research and Management (IJSRM), 2021)
The research conducted to assess the impact of e-Learning on the teaching and learning management in primary education in Rwanda. The researcher must test the validity of the learning using expert validation sheet instruments and limited testing using observation sheets, interview guides, questionnaires and documentation as the main instruments. Data analysis was conducted using descriptive analysis techniques. E-learning is able to generate a high attractiveness and high learning motivation for the students. respondents to give their level of agreement to the statements relate to factors to that influence e-learning teaching management materials, it was revealed that 47.9% strongly agree that there is management of eLearning in their respective schools, 35.4% agree with the statement and 16.7% disagree that in Management of eLearning in your school with mean of 4.58 and a standard deviation of 0.43. Learner’s perspective on learning using e-learning, E-Learning teaching materials, Teacher perspective on teaching using e-Learning. (F=7.761, p value =0.000) shows that there is a significant relationship between p existing Learner’s perspective on learning using e-learning, E-Learning teaching materials, Learner’s perspective on learning using e-learning.at least one of the slope is not zero.Key words: E-learning, Learning Materials, Management of Primary Education.